Impact Digital Transformation in Agricultural Product Marketing in Increase Sustainability Economy Village - Maula, Indi Millatul (Politeknik Siber Cerdika Internasional, 2024)
Digital transformation has play role important in various sectors , including marketing results agriculture , which provides opportunity big For increase sustainability economy village . In Indonesia, there are many farmer small face constraint market access and distribution , while digitalization offer solution potential For expand market reach and increase income . Research This aiming For analyze impact digital transformation in marketing results agriculture to sustainability economy village , with focus on improvement income farmers , efficiency chain distribution , and barriers adoption technology . Using method quantitative descriptive , primary data collected through survey to farmers in several areas as well interview structured For to obtain understanding more in related challenges faced . Research results show that digitalization marketing has increase average farmer income up to 30%, especially with reduce dependence on intermediaries . However , the constraints like low digital literacy and limitations internet access still become obstacle main . Research This highlight importance support digital infrastructure and training for optimize benefit digital transformation in the sector agriculture village . Implications study This covers recommendation policy For strengthen economy rural through inclusive and sustainable digitalization